Manganese-based sodium-ion battery cathode material and preparation method thereof

CN123017935APending Publication Date: 2026-10-30GUANGXI MANGANESE NEW ENERGY TECH DEV CO LTD
View PDF 0 Cites -1 Cited by

Patent Information

Application Number
CN202611293530.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-30

Smart Images

  • Figure CN123017935A_ABST
    Figure CN123017935A_ABST
Patent Text Reader

Abstract

The application discloses a manganese-based sodium ion battery positive electrode material and a preparation method thereof, and belongs to the technical field of sodium ion batteries for vehicles. 0.44 The manganese-based sodium ion battery positive electrode material is based on a titanium foil, is composed of Na-birnessite layered two-dimensional nanosheets and Na MnO2 tunnel type one-dimensional nanowires in-situ symbiosis, one-dimensional nanowires grow from the surface and edge of two-dimensional nanosheets. The application first prepares a wet-state layered precursor, and then performs hydrothermal treatment in a high-concentration alkali solution containing an auxiliary sodium source. By precisely controlling the reaction temperature and time, incomplete topological transformation is realized, and phase change is terminated by rapid quenching. The layered / tunnel symbiotic heterostructure is controllably obtained, the high capacity of the layered phase and the high stability of the tunnel phase are coordinated, and the specific capacity, rate and cycle performance are significantly improved. The application solves the defects of poor cycle stability of the pure layered phase and low capacity of the pure tunnel phase, and combines the advantages of the two phases. The process is controllable, and is suitable for sodium ion energy storage batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium-ion battery technology for automobiles, and in particular to a manganese-based sodium-ion battery cathode material and its preparation method. Background Technology

[0002] Sodium-ion batteries are considered one of the most promising alternative technologies in the fields of large-scale energy storage and new energy vehicles due to the abundance of sodium resources, low cost, and similar working principle to lithium-ion batteries.

[0003] In 2025, CATL released its second-generation sodium-ion battery, "Sodium New," with a cell energy density of 175Wh / kg, a capacity retention rate of over 90% in extremely cold environments down to -40℃, and a cycle life exceeding 10,000 cycles. This battery has passed GB 38031-2025 "Safety Requirements for Power Batteries for Electric Vehicles" certification, becoming the world's first sodium-ion battery to pass the new national standard certification.

[0004] In February 2026, Changan Automobile and CATL jointly launched the world's first mass-produced passenger vehicle equipped with sodium-ion batteries, marking the official entry of sodium batteries into the core field of new energy vehicle power. Meanwhile, experts pointed out that sodium batteries are not intended to replace lithium batteries, but rather to form a synergistic "sodium-lithium complementary" structure. Lithium batteries will focus on long-range, high-performance applications, while sodium batteries will focus on cost-sensitive, high-safety, and cold-weather applications.

[0005] Layered manganese-based oxides (such as manganese-rich layered sodium ion transition metal oxides Na) x TMO2 is considered one of the most promising candidate materials among many cathode material systems due to its high specific capacity, simple synthesis, and low cost. However, this type of material is prone to irreversible phase transitions during high-voltage charge and discharge, leading to lattice stress accumulation and microcrack nucleation within the crystals. Simultaneously, its poor air stability means it easily reacts with H2O / CO2 when exposed to humid environments, generating surface alkaline impurities that deteriorate electrode processing performance and cycle stability. These inherent defects severely restrict the practical application of layered manganese-based cathode materials in the field of new energy vehicles.

[0006] To address the aforementioned issues, existing technologies have developed modification strategies such as elemental doping and surface coating. Traditional coating methods, such as wet coating and solid-phase coating, struggle to form uniform and dense coating layers, resulting in weak adhesion between the coating layer and the substrate and limited protective effects. In recent years, researchers have utilized Nasicon structure materials with rapid sodium ion diffusion channels, such as NaTi2(PO4)3, to modify the surface of layered cathodes, demonstrating potential in improving rate performance and cycle stability. Furthermore, constructing layered / tunnel heterogeneous co-structures by controlling synthesis conditions, leveraging the synergistic effect of the two phases to balance capacity and structural stability, is also an emerging research direction.

[0007] Therefore, developing a manganese-based sodium-ion battery cathode material that can balance high capacity, long cycle life, and excellent rate performance is of great significance for promoting the large-scale application of sodium batteries in new energy vehicles. Summary of the Invention

[0008] The purpose of this invention is to address the shortcomings of existing technologies by proposing a manganese-based sodium-ion battery cathode material and its preparation method.

[0009] To achieve the above objectives, the present invention adopts the following technical solution: This invention first proposes a manganese-based sodium-ion battery cathode material, wherein the manganese-based sodium-ion battery cathode material is an in-situ symbiotic heterostructure of layered manganese-based oxide and tunnel-type manganese-based oxide, wherein the layered manganese-based oxide exists in the form of two-dimensional nanosheets and the tunnel-type manganese-based oxide exists in the form of one-dimensional nanowires. The one-dimensional nanowires are grown in situ from the surface or edge of the two-dimensional nanosheets, and the two phases are directly connected at the interface to form a symbiotic structure; the mass ratio of tunnel-type manganese-based oxide in the cathode material is 18% to 25%.

[0010] Preferably, the layered manganese-based oxide is Na-birnessite type layered sodium manganate with space group P63 / mmc and interlayer spacing of 0.70–0.74 nm; the tunnel-type manganese-based oxide is Na… 0.44 MnO2, space group Pbam, has a three-dimensional skeleton structure consisting of large S-shaped tunnels and small pentagonal tunnels.

[0011] Preferably, the two-dimensional nanosheet has a thickness of 5-20 nm and a lateral dimension of 100-500 nm; the one-dimensional nanowire has a diameter of 30-80 nm, a length of 200-800 nm, and grows along the

[001] crystal orientation.

[0012] Preferably, the positive electrode material is grown in situ on a titanium foil substrate to form a self-supporting array structure, so that no binder or conductive agent needs to be added when it is used as the working electrode of a sodium-ion battery.

[0013] This invention also proposes a method for preparing the aforementioned manganese-based sodium-ion battery cathode material, comprising the following steps: (1) Titanium foil pretreatment: After cutting the titanium foil, it is polished and ultrasonically cleaned, and then covered with polytetrafluoroethylene tape on one side for later use; Mechanical grinding removes the TiO2 passivation layer from the surface, exposing the fresh metallic Ti surface. At the same time, it generates micro-roughness, which increases the nucleation sites during subsequent hydrothermal growth, improves the bonding force between the active material and the substrate, and reduces the interfacial contact resistance.

[0014] (2) Preparation of layered precursor: KMnO4 and NaOH were dissolved in deionized water to prepare solution A, and MnSO4·H2O was dissolved in deionized water to prepare solution B; solution B was added dropwise to solution A under vigorous stirring, and stirring and aging continued after the addition was completed. After centrifugation and washing, wet Na-birnessite layered precursor was obtained. When solution A (KMnO4 + NaOH) is mixed with solution B (MnSO4), a disproportionation reaction occurs:

[0015] Under strongly alkaline conditions (3M NaOH), MnO2 reacts with Na... + H2O and other elements combine to form layered sodium birnessite:

[0016] In strongly alkaline high Na + In a concentration environment, Na + Water molecules are embedded between the MnO6 octahedral layers, expanding the interlayer spacing along the c-axis while inhibiting stacking growth along the c-axis and promoting two-dimensional expansion; (001) the basal surface has the lowest surface energy and the slowest growth rate, eventually becoming the exposed surface; the side surface (hk0) grows quickly, resulting in a lateral dimension much larger than the thickness, forming a two-dimensional nanosheet morphology; therefore, the MnO6 octahedron preferentially grows into a two-dimensional layered structure; during the 24h aging period, small particles dissolve and large particles grow, the crystallinity of the layered structure increases, and the sheets become more regular and uniform.

[0017] (3) Hydrothermal topological transformation: The wet Na-birnessite layered precursor is dispersed in a concentrated NaOH solution containing an auxiliary sodium source to form a uniform suspension; the pretreated titanium foil is vertically immersed in the suspension and placed in a hydrothermal reactor and kept at 170-190℃ for 5.5-6.0 hours to allow the layered precursor to undergo an incomplete topological transformation, resulting in a structure in situ coexistence of layered manganese-based oxide two-dimensional nanosheets and tunnel-type manganese-based oxide one-dimensional nanowires; In a concentrated alkaline environment, alkaline dissolution occurs at the edges / defects of the MnO6 octahedral layer, the Mn-O bonds break, and manganese species enter the solution in the form of soluble manganate / manganite ions; the Mn originally present in the layer... 3+ Disproportionation occurs:

[0018] Mn 2+ Because of its large radius (0.83Å) and low charge, it detaches from the plate and migrates into the interlayer space or solution, leaving a large number of cation vacancies in the MnO6 plate. The vacancy density increases over time, and the stress inside the plate continues to accumulate.

[0019] When the vacancy density reaches a critical threshold, the layered structure cannot maintain its original topology, and the MnO6 octahedral arrangement becomes misaligned, disrupting the stacking period between layers. Vacancies cause local lattice distortion, generating in-plane compressive / tensile stress. When the stress exceeds the tolerance limit of the layered structure, the MnO6 octahedrons undergo large-scale rearrangement.

[0020] The layered Birnessite MnO6 octahedrons reassemble via a dissolution-recrystallization mechanism, with the laminations fracturing at vacancy-dense locations, and the MnO6 octahedral units dissolving as soluble manganate salts. The dissolved manganese species are redeposited at energy-favorable sites, arranging themselves in a tunnel-like topological configuration. The MnO6 octahedrons and MnO5 tetragonal pyramids together construct a three-dimensional framework (space group Pbam) with large S-shaped tunnels and small pentagonal tunnels. Na + It occupies the Na1, Na2 (S-shaped tunnel), and Na3 (pentagonal tunnel) sites within the tunnel. Within a time window of 5.5–6.0 h, the system is in an intermediate state of "sheets not completely disappearing and lines being generated in large numbers," which is the target symbiotic structure.

[0021] If the reaction continues, the layered two-dimensional nanosheets are completely consumed and transformed into the tunneling phase. The one-dimensional nanowires further thicken and lengthen through Ostwald ripening, and after 12 hours, the product is pure Na. 0.44 One-dimensional MnO2 nanowires with a diameter of 50–70 nm and a length of 200–500 nm.

[0022] Na 0.44 The tunnel structure of MnO2 extends along the c-axis. When growing along the

[001] direction, the tunnel structure extends continuously and the growth energy barrier is the lowest. Lateral growth (perpendicular to the c-axis) requires the construction of a new tunnel cross section, which has a higher energy barrier. Therefore, one-dimensional nanowires naturally grow along the

[001] direction to form a one-dimensional linear morphology.

[0023] (4) Quenching termination: After the preset holding time is reached, the hydrothermal reactor is taken out of the oven and immersed in a cold water bath for rapid quenching. The temperature of the reactor body is reduced to below 60°C within 30 to 60 seconds to terminate the phase transformation. If the body cools naturally, the reaction continues slowly during the cooling process. The residual heat will cause the layered phase to continue to transform, deviating from the target two-phase ratio. Other solid phases may even diffuse during the cooling process, introducing impurities.

[0024] (5) Post-processing: Remove the titanium foil, rinse and dry it to obtain the titanium foil-loaded layered / tunnel symbiotic manganese-based sodium-ion battery cathode material.

[0025] The layered phase (P63 / mmc) and the tunnel phase (Pbam) are not in simple physical contact at the interface. Both phases use MnO6 octahedra as the basic building blocks, and the octahedra can transition continuously at the interface to form a coherent / semi-coherent interface. The lamellar sheets of the layered phase are embedded in the framework of the tunnel phase, mechanically interlocked, similar to a mortise and tenon structure. During charging and discharging, the volume expansion of the layered phase is constrained by the rigid tunnel framework, and the micro-strain of the tunnel phase is absorbed by the flexible layered phase, which greatly improves the overall structural stability.

[0026] Preferably, in step (2), the concentration of KMnO4 in solution A is 0.08–0.12 mol / L, and the concentration of NaOH is 2.5–3.5 mol / L; the concentration of MnSO4 in solution B is 0.25–0.30 mol / L; the dropping rate of solution B is 1–5 mL / min; the aging time is 12–36 h; and the wet Na-birnessite layered precursor has a water content of 60%–80% and is used directly in the next hydrothermal reaction without drying.

[0027] Preferably, in step (3), the concentration of the concentrated NaOH solution is 12-18 mol / L; the auxiliary sodium source is selected from at least one of Na2C2O4, Na2CO3, and NaNO3, and its concentration in the solution is 0.03-0.10 mol / L; the amount of wet Na-birnessite precursor added is 1.5-2.5 g per 50 mL of alkaline solution.

[0028] In the auxiliary sodium source (Na2C2O4), C2O4 2- It is a mild reducing agent, which can reduce some of the Mn under concentrated alkali and high temperature. 4+ Restored to Mn 3 + C2O4 2- Na is released after decomposition / reaction. + Change local Na + Concentration, sufficient Na + The supply is conducive to the nucleation and growth of tunnel facies.

[0029] The present invention also proposes a sodium-ion battery comprising a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the positive electrode comprises the aforementioned manganese-based sodium-ion battery positive electrode material.

[0030] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention constructs a heterostructure in situ coherently grown layered two-dimensional nanosheets and tunneled one-dimensional nanowires by precisely capturing the metastable symbiotic window during the topological transition from layered to tunneled phases. The direct lattice overlap at the interface of the two phases forms a continuous low-barrier sodium ion migration channel, which significantly reduces the interfacial impedance. At the same time, the layered phase provides high-density sodium storage active sites, and the tunneled phase provides a three-dimensional rigid framework to buffer volumetric strain. The synergistic stress dissipation mechanism of the two phases during the charging and discharging process effectively suppresses the nucleation and propagation of microcracks within the crystals, thereby simultaneously improving the specific capacity, rate performance, and cycle stability of the material.

[0031] Compared with existing technologies, conventional layered manganese-based oxides, while possessing high specific capacity, are prone to irreversible P2-O2 phase transitions during high-voltage deep sodium removal, leading to lattice collapse and a sharp capacity decay; while single tunnel-type Na 0.44 Although MnO2 has a stable structure, its theoretical specific capacity is only about 120 mAh / g, which is insufficient to meet the energy density requirements of power batteries. This invention constructs a two-phase system with a sheet-wire coexistence, where the layered phase contributes high capacity while the tunnel phase maintains the structural framework. The lattice strain fields between the two phases cancel each other out, thus decoupling the contradiction between capacity and stability.

[0032] 2. This invention uses layered Na-birnessite two-dimensional nanosheets as a self-sacrificing template, and then, under concentrated alkaline hydrothermal conditions, utilizes Mn... 3+ Charge disproportionation-driven in-situ topological transition enables tunneled Na 0.44 One-dimensional MnO2 nanowires are epitaxially grown from the edges and surfaces of two-dimensional nanosheets to form a chemically bonded coherent interface rather than a physically adsorbed coating layer. This in-situ construction method ensures the atomic-scale lattice continuity between the coating layer and the substrate, avoiding the interface debonding and additional contact resistance caused by lattice mismatch in traditional coating methods, thereby giving the material higher structural integrity and interface stability.

[0033] Existing surface coating technologies, such as the sol-gel method and solid-state sintering method, typically involve the physical deposition of Nasicon phases such as NaTi2(PO4)3 on the surface of a layered cathode. The coating layer and the substrate only have mechanical contact, lacking chemical bonding, making them prone to peeling and failure during long-term cycling. Furthermore, coating layers prepared by traditional methods are often inert phases with ionic conductivity far lower than the substrate, potentially becoming bottleneck layers for sodium ion transport.

[0034] This invention utilizes a "sacrificial template-in-situ transformation" strategy to form a sheet-line coexistence structure. The two phases achieve atomic-level bonding with lattice continuity through coherent grain boundaries, eliminating interfacial contact resistance and leveraging the high ionic conductivity of the tunnel phase itself. Na 0.44The S-shaped tunneling diffusion barrier of MnO2 is much lower than that of the layered phase, providing a relay-style low-resistivity transport path for sodium ions from the layered phase to the tunneling phase, thus solving the technical problem of interface compatibility between the coating layer and the matrix in the prior art.

[0035] 3. This invention constructs a self-supporting integrated electrode without the need for conductive agents and binders by in-situ growing sheet-wire symbiotic cathode materials on the surface of a titanium foil current collector. The high specific surface area of ​​the two-dimensional nanosheets ensures sufficient contact between the active material and the electrolyte and shortens the solid-phase diffusion distance of sodium ions. The continuous network structure of the one-dimensional nanowires runs through the entire thickness direction of the electrode, constructing a long-range electronic conduction pathway. The interconnected network topology of the sheet-wires provides abundant electrochemical active interfaces and efficient electron / ion dual continuous transport channels, thereby maximizing the utilization rate of active materials and minimizing polarization resistance at the electrode level. This is particularly suitable for the power battery requirements of new energy vehicles for high power density and long cycle life.

[0036] In existing technologies, layered manganese-based cathodes typically require composite molding with conductive carbon black and PVDF binders. Inactive components usually account for 20%–30% of the total electrode mass, which not only dilutes the electrode's energy density but also blocks direct electronic contact between active particles, increasing internal contact impedance. Furthermore, the introduction of binders can cause interfacial compatibility issues such as electrolyte swelling and high-pressure oxidative decomposition. This invention directly hydrothermally grows the active array on conductive titanium foil, eliminating the electrode slurry coating process and removing the parasitic impedance of inactive components. The high specific surface area provided by the two-dimensional nanosheets contributes additional capacity for rapid pseudocapacitive sodium storage, while the three-dimensional conductive network composed of one-dimensional nanowires ensures electron supply at high rates. Together, these two elements achieve high utilization of the active materials. This binder-free integrated electrode design is suitable for the stringent requirements of new energy vehicles in terms of instantaneous power output and long-term reliability under high-rate conditions such as low-temperature start-up and rapid acceleration. Attached Figure Description

[0037] Figure 1 This is a TEM image of the manganese-based sodium-ion battery cathode material obtained in Comparative Example 1 of this invention; Figure 2 This is a TEM image of the manganese-based sodium-ion battery cathode material obtained in Example 1 of the present invention; Figure 3 This is a TEM image of the manganese-based sodium-ion battery cathode material obtained in Comparative Example 2 of this invention. Detailed Implementation

[0038] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0039] Example 1:

[0040] (1) Titanium foil pretreatment: Cut the titanium foil into 2cm×3cm rectangles, lightly sand it with 400# sandpaper to remove the TiO2 passivation film on the surface; sonicate it in anhydrous ethanol, 2M HCl and deionized water for 15 minutes each in sequence; apply PTFE polytetrafluoroethylene tape mask to one side and soak it in deionized water for later use.

[0041] (2) Preparation of layered precursor: KMnO4 and NaOH were dissolved in deionized water to prepare solution A, and MnSO4·H2O was dissolved in deionized water to prepare solution B; solution B was added dropwise to solution A under vigorous stirring, and stirring and aging continued after the addition was completed. After centrifugation and washing, wet Na-birnessite layered precursor was obtained. (3) Hydrothermal topological transformation: The wet Na-birnessite layered precursor was dispersed in a concentrated NaOH solution containing an auxiliary sodium source to form a uniform suspension; the pretreated titanium foil was vertically immersed in the suspension and placed in a hydrothermal reactor and kept at 180°C for 5.8 hours to allow the layered precursor to undergo an incomplete topological transformation, resulting in a structure in situ coexistence of layered manganese oxide two-dimensional nanosheets and tunnel-type manganese oxide one-dimensional nanowires; (4) Quenching termination: After the preset holding time is reached, the hydrothermal reactor is taken out of the oven and immersed in a cold water bath for rapid quenching. The temperature of the reactor body is reduced to below 60°C within 45 seconds to terminate the phase transformation. (5) Post-processing: Remove the titanium foil, rinse and dry it to obtain the titanium foil-loaded layered / tunnel symbiotic manganese-based sodium-ion battery cathode material.

[0042] In step (2), the concentration of KMnO4 in solution A is 0.10 mol / L and the concentration of NaOH is 3 mol / L; the concentration of MnSO4 in solution B is 0.28 mol / L; the dropping rate of solution B is 3 mL / min; the aging time is 24 h; the wet Na-birnessite layered precursor has a water content of 70% and is used directly in the next hydrothermal reaction without drying.

[0043] In step (3), the concentration of the concentrated NaOH solution is 15 mol / L; the auxiliary sodium source is Na2C2O4, and its concentration in the solution is 0.06 mol / L; the amount of wet Na-birnessite precursor added is 2 g per 50 mL of alkaline solution.

[0044] Example 2:

[0045] (1) Titanium foil pretreatment: Cut the titanium foil into 2cm×3cm rectangles, lightly sand it with 400# sandpaper to remove the TiO2 passivation film on the surface; sonicate it in anhydrous ethanol, 2M HCl and deionized water for 15 minutes each in sequence; apply PTFE polytetrafluoroethylene tape mask to one side and soak it in deionized water for later use.

[0046] (2) Preparation of layered precursor: KMnO4 and NaOH were dissolved in deionized water to prepare solution A, and MnSO4·H2O was dissolved in deionized water to prepare solution B; solution B was added dropwise to solution A under vigorous stirring, and stirring and aging continued after the addition was completed. After centrifugation and washing, wet Na-birnessite layered precursor was obtained. (3) Hydrothermal topological transformation: The wet Na-birnessite layered precursor was dispersed in a concentrated NaOH solution containing an auxiliary sodium source to form a uniform suspension; the pretreated titanium foil was vertically immersed in the suspension and placed in a hydrothermal reactor and kept at 170°C for 6.0 hours to allow the layered precursor to undergo an incomplete topological transformation, resulting in a structure in situ coexistence of layered manganese-based oxide two-dimensional nanosheets and tunnel-type manganese-based oxide one-dimensional nanowires; (4) Quenching termination: After the preset holding time is reached, the hydrothermal reactor is taken out of the oven and immersed in a cold water bath for rapid quenching. The temperature of the reactor body is reduced to below 60°C within 30 seconds to terminate the phase transformation. (5) Post-processing: Remove the titanium foil, rinse and dry it to obtain the titanium foil-loaded layered / tunnel symbiotic manganese-based sodium-ion battery cathode material.

[0047] In step (2), the concentration of KMnO4 in solution A is 0.08 mol / L and the concentration of NaOH is 3.5 mol / L; the concentration of MnSO4 in solution B is 0.25 mol / L; the dropping rate of solution B is 5 mL / min; the aging time is 36 h; the wet Na-birnessite layered precursor has a water content of 80% and is used directly in the next hydrothermal reaction without drying.

[0048] In step (3), the concentration of the concentrated NaOH solution is 12 mol / L; the auxiliary sodium source is NaNO3, and its concentration in the solution is 0.03 mol / L; the amount of wet Na-birnessite precursor added is 2.5 g per 50 mL of alkaline solution.

[0049] Example 3:

[0050] (1) Titanium foil pretreatment: Cut the titanium foil into 2cm×3cm rectangles, lightly sand it with 400# sandpaper to remove the TiO2 passivation film on the surface; sonicate it in anhydrous ethanol, 2M HCl and deionized water for 15 minutes each in sequence; apply PTFE polytetrafluoroethylene tape mask to one side and soak it in deionized water for later use.

[0051] (2) Preparation of layered precursor: KMnO4 and NaOH were dissolved in deionized water to prepare solution A, and MnSO4·H2O was dissolved in deionized water to prepare solution B; solution B was added dropwise to solution A under vigorous stirring, and stirring and aging continued after the addition was completed. After centrifugation and washing, wet Na-birnessite layered precursor was obtained. (3) Hydrothermal topological transformation: The wet Na-birnessite layered precursor is dispersed in a concentrated NaOH solution containing an auxiliary sodium source to form a uniform suspension; the pretreated titanium foil is vertically immersed in the suspension and placed in a hydrothermal reactor and kept at 190°C for 5.5 hours to allow the layered precursor to undergo an incomplete topological transformation, resulting in a structure in situ coexistence of layered manganese-based oxide two-dimensional nanosheets and tunnel-type manganese-based oxide one-dimensional nanowires; (4) Quenching termination: After the preset holding time is reached, the hydrothermal reactor is taken out of the oven and immersed in a cold water bath for rapid quenching. The temperature of the reactor body is reduced to below 60°C within 60 seconds to terminate the phase transformation. (5) Post-processing: Remove the titanium foil, rinse and dry it to obtain the titanium foil-loaded layered / tunnel symbiotic manganese-based sodium-ion battery cathode material.

[0052] In step (2), the concentration of KMnO4 in solution A is 0.12 mol / L and the concentration of NaOH is 2.5 mol / L; the concentration of MnSO4 in solution B is 0.30 mol / L; the dropping rate of solution B is 1.5 mL / min; the aging time is 12 h; the wet Na-birnessite layered precursor has a water content of 60% and is used directly in the next hydrothermal reaction without drying.

[0053] In step (3), the concentration of the concentrated NaOH solution is 18 mol / L; the auxiliary sodium source is Na2CO3, and its concentration in the solution is 0.10 mol / L; the amount of wet Na-birnessite precursor added is 1.5 g per 50 mL of alkaline solution.

[0054] The following comparison model was also set: Comparative Example 1: The hydrothermal reaction time was too short (4.0 h, phase change did not start), the rest was the same as in Example 1.

[0055] Comparative Example 2: The hydrothermal reaction time was too long (7.0 h, the layered precursor was completely consumed), the rest was the same as in Example 1.

[0056] Comparative Example 3: The hydrothermal temperature was too high (200°C, phase change was uncontrolled and rapidly and completely converted), the rest was the same as in Example 1.

[0057] Comparative Example 4: The alkali concentration was too low (8 mol / L NaOH, which could not drive the topological transformation), and the rest was the same as in Example 1.

[0058] Comparative Example 5: No rapid quenching, natural cooling to terminate the reaction, the rest is the same as Example 1.

[0059] Comparative Example 6: No auxiliary sodium source was added, and the rest was the same as in Example 1.

[0060] Performance testing: Using the positive electrode material of the battery obtained in this invention as the electrode, the active loading is 1.8 ± 0.2 mg·cm⁻¹. -2 A half-cell system was constructed using a sodium metal counter electrode, a GF / D glass fiber membrane, and 1M NaPF6 (EC:DEC:FEC=1:1:0.05). The initial capacity at 0.1C, the long-term cycling at 5C for 300 cycles, the EIS charge transfer impedance Rct, and the GITT sodium ion diffusion coefficient D were tested.

[0061] Table 1. Relevant test data for each experimental group

[0062] Data Analysis: for Figure 1 The main body consists of large-area, thin-layered Na-birnessite two-dimensional nanosheets, with only a very small number of short needle-like nascent structures emerging from the edges of the sheets. Due to insufficient topological transition time, the layered precursors hardly underwent rearrangement, resulting in tunnel-type Na... 0.44 The nucleation rate of MnO2 is extremely low. The structure is dominated by a pure layered phase, and the two-dimensional sheets are prone to structural collapse during charge and discharge. The corresponding electrochemical data show high initial capacity but poor cycle stability.

[0063] for Figure 2 The in-situ symbiotic characteristics of two-dimensional nanosheets and one-dimensional nanowires can be clearly observed: thin, layered oxide sheets serve as the substrate, while one-dimensional nanowires grow outward from the edges and surfaces of the two-dimensional nanosheets, with the sheets and wires tightly connected, indicating that it is not a simple physical mixture of two powders. The thickness of the two-dimensional nanosheets and the size of the one-dimensional nanowires both fall within the range defined in the patent, forming a continuous and interconnected conductive network. This in-situ heterostructure combines the high sodium storage activity sites of the layered phase with the framework stability of the tunnel phase, matching the relevant electrochemical performance.

[0064] for Figure 3 The thin two-dimensional nanosheets are almost invisible in the image; the product is entirely transformed into one-dimensional needle / wire-like Na. 0.44 MnO2, the layered precursor, is completely consumed. The pure tunnel one-dimensional nanowire structure has a stable three-dimensional framework and excellent cycle retention; however, the lack of a high-capacity layered phase reduces the number of active sites, directly resulting in a significant decrease in the initial discharge capacity.

[0065] All three examples yielded layered / tunnel in-situ symbiotic heterostructure cathodes. The initial 0.1C discharge capacity of Examples 1–3 reached 174.3–182.1 mAh g⁻¹. -1 At 5C, the capacity retention rate remained stable at 69.8%–71.2% after 300 cycles; the charge transfer impedance Rct was 72.1–86.7 Ω, and Na… + The diffusion coefficient is 1.38 × 10⁻⁶. -14 ~1.75×10 -14 cm 2 s -1 Within the range, the overall electrochemical performance is balanced and excellent.

[0066] Comparative Examples 1 and 4 are near-pure layered materials with relatively high initial capacities (>187 mAh g). -1 However, the cycle stability is extremely poor, with a capacity retention of less than 44% after 300 cycles. The ion diffusion coefficient decreases by an order of magnitude, and the layered structure is prone to distortion and collapse during charge and discharge. Comparative Examples 2 and 3 are completely transformed into pure tunneling phases, resulting in improved structural stability and a cycle retention rate higher than 76%. However, due to the lack of capacity contribution from the layered phase, the initial discharge capacity is only 105–113 mAhg. -1 .

[0067] Comparative Example 5, which eliminated rapid quenching, and Comparative Example 6, which did not add an auxiliary sodium source, showed that the ratio of the two phases deviated from the optimal range, making it impossible to form an ideal sheet-wire symbiotic interface. At the same time, they exhibited defects such as low capacity, accelerated cycle decay, and significantly increased impedance.

[0068] Data demonstrates that precise control of hydrothermal conditions to achieve incomplete topological transformation, combined with rapid quenching and auxiliary sodium source regulation, can construct an in-situ symbiotic structure of the tunnel phase. This can integrate the advantages of high capacity of the layered phase and the structural stability of the tunnel phase, reduce interfacial impedance, accelerate sodium ion migration, and achieve a synergistic improvement in capacity and cycle life.

[0069] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A manganese-based sodium-ion battery cathode material, characterized in that, The positive electrode material of the manganese-based sodium-ion battery is an in-situ symbiotic heterostructure of layered manganese oxide and tunnel-type manganese oxide, wherein the layered manganese oxide exists in the form of two-dimensional nanosheets and the tunnel-type manganese oxide exists in the form of one-dimensional nanowires. The one-dimensional nanowires are grown in situ from the surface or edge of the two-dimensional nanosheets, and the two phases are directly connected at the interface to form a symbiotic structure; in the manganese-based sodium ion battery cathode material, the mass ratio of tunnel-type manganese-based oxide is 18% to 25%.

2. The manganese-based sodium-ion battery cathode material according to claim 1, characterized in that, The layered manganese-based oxide is Na-birnessite type layered sodium manganate, space group P63 / mmc, with an interlayer spacing of 0.70–0.74 nm; the tunnel-type manganese-based oxide is Na… 0.44 MnO2, space group Pbam, has a three-dimensional skeleton structure consisting of large S-shaped tunnels and small pentagonal tunnels.

3. The manganese-based sodium-ion battery cathode material according to claim 1, characterized in that, The two-dimensional nanosheets have a thickness of 5–20 nm and a lateral dimension of 100–500 nm; the one-dimensional nanowires have a diameter of 30–80 nm, a length of 200–800 nm, and grow along the [001] crystal orientation.

4. The manganese-based sodium-ion battery cathode material according to claim 1, characterized in that, The positive electrode material is grown in situ on a titanium foil substrate to form a self-supporting array structure, which eliminates the need for binders and conductive agents when used as a working electrode in a sodium-ion battery.

5. A method for preparing a manganese-based sodium-ion battery cathode material as described in any one of claims 1 to 4, characterized in that, Includes the following steps: (1) Titanium foil pretreatment: After cutting the titanium foil, it is polished and ultrasonically cleaned, and then covered with polytetrafluoroethylene tape on one side for later use; (2) Preparation of layered precursor: KMnO4 and NaOH were dissolved in deionized water to prepare solution A, and MnSO4·H2O was dissolved in deionized water to prepare solution B; solution B was added dropwise to solution A under vigorous stirring, and stirring and aging continued after the addition was completed. After centrifugation and washing, wet Na-birnessite layered precursor was obtained. (3) Hydrothermal topological transformation: The wet Na-birnessite layered precursor is dispersed in a concentrated NaOH solution containing an auxiliary sodium source to form a uniform suspension; The pretreated titanium foil was vertically immersed in the suspension and placed in a hydrothermal reactor and kept at 170–190°C for 5.5–6.0 hours to induce an incomplete topological transformation of the layered precursor, resulting in a structure in situ coexistence of layered manganese oxide and tunnel-type manganese oxide. (4) Quenching termination: After the preset holding time is reached, the hydrothermal reactor is taken out of the oven and immersed in a cold water bath for rapid quenching. The temperature of the reactor body is reduced to below 60°C within 30 to 60 seconds to terminate the phase transformation. (5) Post-processing: Remove the titanium foil, rinse and dry it to obtain the titanium foil-loaded layered / tunnel symbiotic manganese-based sodium-ion battery cathode material.

6. The preparation method according to claim 5, characterized in that, In step (2), the concentration of KMnO4 in solution A is 0.08–0.12 mol / L, and the concentration of NaOH is 2.5–3.5 mol / L; the concentration of MnSO4 in solution B is 0.25–0.30 mol / L; the dropping rate of solution B is 1–5 mL / min; the aging time is 12–36 h; the water content of the wet Na-birnessite layered precursor is 60%–80%, and it is used directly in the next hydrothermal reaction without drying.

7. The preparation method according to claim 5, characterized in that, In step (3), the concentration of the concentrated NaOH solution is 12-18 mol / L; the auxiliary sodium source is selected from at least one of Na2C2O4, Na2CO3, and NaNO3, and its concentration in the solution is 0.03-0.10 mol / L; the amount of wet Na-birnessite precursor added is 1.5-2.5 g per 50 mL of alkaline solution.

8. A sodium-ion battery, comprising a positive electrode, a negative electrode, a separator, and an electrolyte, characterized in that, The positive electrode comprises the manganese-based sodium-ion battery positive electrode material according to any one of claims 1 to 4.